CLINICAL COURSE OF SYSTEMIC LUPUS ERYTHEMATOSUS IN CHILDREN IN THE CONTEXT OF IMMUNOLOGICAL DISORDERS: DIFFERENTIAL DIAGNOSTIC CRITERIA (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The study is devoted to the clinical and immunological features of systemic lupus erythematosus (SLE) in children in order to clarify the differential diagnostic criteria. It was found that the disease often manifests itself at school age and is characterized by pronounced clinical polymorphism with the involvement of the skin, joints and internal organs. Reliable immunological shifts were revealed - an increase in the levels of acute phase proteins, a decrease in complement components, as well as an increase in the titers of antinuclear and anti-DNA antibodies. The data obtained emphasize the importance of a comprehensive assessment of clinical and immunological markers in the early diagnosis of SLE. This allows timely initiation of pathogenetic therapy and prevention of the development of severe complications.